Pro Java™ 6 3D Game Development: Java 3D™, JOGL, JInput, and JOAL APIs - Davison, Andrew (Apress, 2012)
If you’re not persuaded yet, how about a managerial-style, one-sentence summary of the book: My aim is to describe the key building blocks needed to create fun, exciting 3D games in Java on a PC, with an emphasis on the construction of 3D landscapes that a player can explore. If that’s not enough (gosh, you’re a tough customer), cast your eyes over the next section (but really, there’s no need; this book was meant for you).